Mona Lisa’s Mysterious Smile: The Artist Initiate in Esoteric New Religions - Faxneld, Per (Nova religio, 2016)
The article discusses the view, held by many nineteenth-century authors, of Leonardo da Vinci as an esotericist, and his La Gioconda as mysterious, sinister and filled with hidden signs. This “esoterization” of the painting and its creator was part of a broader tendency to view artists, both historical and contemporary, as magicians and mystics in some sense. Hereby, art became integrated into the endeavors of various esoteric groups and thinkers, and an originally secular Renaissance work was absorbed into a nineteenth-century “occulture” or “cultic milieu.”